Frekuensi Kehadiran Arthropoda pada Media Dekomposisi Pelepah Nipah (Nypa fruticans) di Kawasan Mangrove Sungai Kakap Kalimantan Barat - Mulyani, Lastyanti; Junardi, Junardi; Kurniatuhadi, Rikhsan (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to determine the frequency of Arthropod occurrence at each stage of decomposition and to assess its relationship with environmental parameters in the mangrove area of Sungai Kakap. Arthropod sampling was conducted using the hand-collecting method on days 15, 25, 35, and 45 after substrate placement. A total of 24 fronds were randomly positioned vertically at a depth of 20 cm below the soil surface, with six replication across four time-based observation points. Arthropod eggs, larvae, pupae, and imago were collected, sorted, and preserved in 70% alcohol. Specimens were identified directly through morphological observation, and the data obtained were analyzed descriptively. The results showed that the Relative Frequency (RF) of Arthropods consisted of 34 genera, dominated by Amphipoda (Allorchestoides: 75% FR) and Diptera (Bactrocera: 75% FR; Eristalinus: 100% FR; Psychoda: 100% FR). An RF of 100% indicates that these genera were consistently present across all observation points and time periods, suggesting their potentially important role in the decomposition process. Variations in Arthropod presence among genera reflect changes in composition at each decomposition stage. These changes were influenced by environmental conditions, particularly salinity, pH, temperature, as well as organic carbon and nitrogen levels. These findings indicate that certain Arthropods have the potential to serve as biological indicators of decomposition stages in mangrove ecosystems. Further research is recommended to investigate microbial dynamics and changes in organic content throughout the decomposition process.